Clinical features and outcomes of cytomegalovirus colitis in adult patients with inflammatory bowel disease - Duaa Bakheet (Bioinformation, 2026)
Cytomegalovirus infection is clinically important in inflammatory bowel disease, but data from the Middle Eastern population are still lacking. This retrospective cross-sectional investigation examined adult patients (≥18 years) treated at King Abdulaziz Medical City, Jeddah, Saudi Arabia, from January 2014 to December 2023 with confirmed CMV colitis and underlying IBD. UC was more common than CD (56.5% vs 43.5%) and pancolitis was the most common illness distribution (52.2%). Deep ulceration was the most prevalent endoscopic finding (60.9%). Most patients (65.2%) received corticosteroids, 26.1% were steroid-refractory. Tissue CMV PCR was positive in 60.9% of patients and serum in 21.7%. Sixteen patients (69.6%) received antiviral therapy. Clinical remission occurred in 81.25% (13/16) of treated individuals. CMV colitis is a serious IBD complication, especially in long-term immunosuppressive patients. Thus, tissue-based diagnostic approaches, especially CMV PCR, detect active infection better than serological assays.